If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 4y = 4 Solving -1x + 4y = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -1x + 4y + -4y = 4 + -4y Combine like terms: 4y + -4y = 0 -1x + 0 = 4 + -4y -1x = 4 + -4y Divide each side by '-1'. x = -4 + 4y Simplifying x = -4 + 4y
| e-t^2+4=0 | | 2x+3+3x+7=75 | | 3(2x-1)-2(2x-4)=19 | | 7(3x-13)=161 | | 8x-7+2x-5=58 | | 16(x-4)=13(x-5) | | 1-2(-2)+3(-5)= | | x-2*3+x-2*2=25 | | -6(-4u+7)-2u=7(u-3)-3 | | 4x+8-2x+7=39 | | e^8=y | | 11x+17=5x-19 | | 2x+86=13 | | 2x+5+x+2=25 | | 8-2m-m^2=0 | | x^2-50x-75=0 | | 2(j-10)=10 | | F(x)=100x-5x^2 | | -8u-12=-4(u-1) | | 7x+11=6x+32 | | 14=2-3r | | 3/x+1=1/2 | | 3(3v+8)-3=6(v+6) | | 7j-5j=18 | | -2(w-4)+6=-4 | | 28-22y=11.6+262.6 | | -2v+-10=9v-21 | | 3n-4=-11 | | Xy-3x=30 | | 9u+10=4u-20 | | 6=-6u+3(u+2) | | y=0.7+1 |